Growth-Enhanced Transgenic Coho Salmon (Oncorhynchus kisutch) Strains Have Varied Success in Simulated Streams: Implications for Risk Assessment - Leggatt, Rosalind A. (PLoS One, 2017)
Growth hormone (GH) transgenic fish have accelerated growth and could improve production efficiency in aquaculture. However, concern exists regarding potential environmental risks of GH transgenic fish should they escape rearing facilities. While environmental effects have been examined in some GH transgenic models, there is a lack of information on whether effects differ among different constructs or strains of transgenic fish. We compared growth and survival of wild-type coho salmon (Oncorhynchus kisutch) fry, a fast-growing GH transgenic strain containing a metallothionein promoter (T(MT)), and three lines/strains containing a reportedly weaker histone-3 promoter (T(H3)) in hatchery conditions and semi-natural stream tanks with varying levels of natural food and predators. Rank order of genotype size and survival differed with varying environmental conditions, both within and among experiments. Despite accelerated growth in hatchery conditions, T(MT) fry gained little or no growth enhancement in stream conditions, had enhanced survival when food was limiting, and inconsistent survival under other conditions. Rank growth was inconsistent in T(H3) strains, with one strain having highest, and two strains having the lowest growth in stream conditions, although all T(H3) strains had consistently poor survival. These studies demonstrate the importance of determining risk estimates for each unique transgenic model independent of other models.